A qualitative study of trainer and trainee perceptions and experiences of clinical assessment in post‐graduate dental training. (15th September 2020) - Amir Rad, Fatemeh A.; Otaki, Farah; AlGurg, Reem; Khan, Erum; Davis, Dave
Abstract: Background: The implementation of workplace‐based assessment (WBA) needs to ensure the achievement of pre‐set competences but may look different across varying contexts, such as in post‐graduate dental education. The purpose of this study is to explore the perception of residents, faculty members and alumni concerning their experience with clinical assessment, and what configurations they consider as optimal to maximise the entailed learning experience. Methods: This study relied on a qualitative descriptive design using two data collection tools: focus group sessions, and semi‐structured, one‐to‐one interviews. Data were triangulated from three sources: residents, faculty members and alumni. The data were inductively analysed based on constructivist epistemology. This was done using the Thematic Analysis approach, facilitated by NVivo software. Results: The analysis revealed two mutually exclusive themes: process and people. Within process, variables related to quality, workflow and feedback surfaced. As for the people theme, the main two group of stakeholders referred to in the related analysis were the trainees and the trainers. Discussion: There are many variables that need to be considered when developing an evidence‐driven WBA. In addition, factoring into the design of the WBA the perception of the main stakeholders will enable contextualisation which is expected to raise the reliability of the adapted tools. Conclusion: This study introduced a framework that could support post‐graduate universities in their journey towards developing context‐specific WBA.